Lease Agreement Characteristics of Virtual Office - Desi Karunia Sari (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2019)
This article is entitled Characteristics of Virtual Office Lease Agreements. This is a normative juridical legal research. The approach used are statute approach and conceptual approach. The problem discussed in this article is Virtual Office lease agreement that uses office addresses as business addresses and make the business address the object of the agreement. In fact, there is no physical address, meaning the object of the agreement is an intangible object that is associated with the validity of the agreement. There are 2 (two) main issues in this research, namely: (1) The concept of objects in a Virtual Office lease agreement rents (2) The application of leasing agreement principle in BW to Virtual Office.